2013
DOI: 10.1111/jai.12265
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale vertical and horizontal movements of juvenile yellowfin tuna (Thunnus albacares ) associated with a subsurface fish aggregating device (FAD) off southwestern Taiwan

Abstract: Summary An increase in yellowfin tuna (Thunnus albacares) catch by danish seine fisheries around the subsurface fish aggregating devices (FADs) in southern Taiwan waters has been a concern of local government and environmental groups. However, the attraction mechanism of aggregating tunas at the subsurface FADs is still poorly understood. The objective of this study is to examine the fine‐scale vertical and horizontal movements of juvenile yellowfin tunas around a subsurface FAD. In total, 53 tunas (35–81 cm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
(33 reference statements)
3
14
0
Order By: Relevance
“…() (skipjack tuna: 0.20–3.75 days, yellowfin tuna: 0.61–0.70 days) and Weng et al . () (yellowfin tuna: up to 31 days, mostly <10 days). In the present study, we observed large temporal changes in species composition and fish size in the catch at FAD6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() (skipjack tuna: 0.20–3.75 days, yellowfin tuna: 0.61–0.70 days) and Weng et al . () (yellowfin tuna: up to 31 days, mostly <10 days). In the present study, we observed large temporal changes in species composition and fish size in the catch at FAD6.…”
Section: Discussionmentioning
confidence: 99%
“…There is potential for the selective harvest of tuna species if their swimming depth differs around FADs. A number of studies have evaluated the vertical behavior of the aforementioned tuna species (the so‐called ‘tropical tunas’) associated with floating objects, including FADs (Cayré and Chabanne, ; Holland et al ., ; Cayré, ; Marsac and Cayré, ; Klimley and Holloway, ; Dagorn et al ., ; Schaefer and Fuller, , , , ; Musyl et al ., ; Ohta and Kakuma, ; Leroy et al ., ; Schaefer et al ., ; Mitsunaga et al ., , ; Matsumoto et al ., ; Weng et al ., ). Most of these studies evaluated the behavior of tropical tunas around anchored FADs whereas few have evaluated behavior around drifting FADs because of the difficulty and expense of tracking FADs.…”
Section: Introductionmentioning
confidence: 97%
“…Graham (2008) estimated the half-life turnover rate of the liver to be shorter than that of muscle tissue (12 versus 63 d), because the metabolic rate of the liver is higher than that of muscle tissue (Suzuki et al 2005;Guelinckx et al 2007). Weng et al (2013) reported that juvenile Yellowfin Tuna that lingered around a single FAD in the waters southwest of Taiwan for >31 d fed on various types of prey during this period and their muscle tissue exhibited varied stable isotope N and C values. The movement of juvenile Yellowfin Tuna from other waters to Taiwanese waters may alter their food intake and increase their nutrient supply.…”
Section: Stable Isotope Analysismentioning
confidence: 99%
“…According to local fishermen's experience, adult yellowfin tuna migrate from the South China Sea to the waters off southwestern Taiwan during the same period. The feeding behaviour of juvenile yellowfin tuna around subsurface FADs in the waters off southwestern Taiwan has been documented (Weng et al, 2013(Weng et al, , 2015. The authors found that juvenile yellowfin tuna aggregated at a depth of 60-80 m in the daytime and at a depth of 40 m at nighttime, and fish stayed near the subsurface FADs for up to 31 days.…”
Section: Introductionmentioning
confidence: 99%